Stereoselective Chemoenzymatic Cascade Synthesis of the bis‐THF Core of Acetogenins. Issue 5 (13th December 2018) - van Lint, Matthijs J.; Hall, Mélanie; Faber, Kurt; van Spanning, Rob J. M.; Ruijter, Eelco; Orru, Romano V. A.
Abstract : bis ‐Tetrahydrofuran acetogenins are a class of natural products displaying highly potent and selective anti‐tumor activity. Herein we report a new route to precursors of these natural products, utilizing the pseudo C 2 ‐symmetry in the central bis ‐tetrahydrofuran fragment. Key steps of our stereoselective chemoenzymatic strategy include the epoxide hydrolase‐mediated desymmetrization of meso‐ epoxides and a cascade cyclization in either "inside‐out" or "outside‐in" direction, providing stereoselective access to the cores of both bullatacin‐ and rolliniastatin 1‐type acetogenins with 6 stereocenters each from a common mono‐epoxide precursor. Abstract : Twice the Payne, double the gain : meso‐ Epoxides can be efficiently desymmetrized using plant epoxide hydrolases. A resulting chiral vicinal diol was used in complementary approaches toward two core structures of acetogenins, natural products with remarkable anti‐tumor activity. Stereodivergence is determined by the directionality of the cyclization cascade.